Syntactic Errors in Simple Sentences of Five-Year-Old Kindergarten Children: A Systematic Literature Review - Zulfatun Anisah (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
This systematic literature review examines syntactic errors in simple spoken sentences produced by five-year-old kindergarten children. Following PRISMA 2020 guidelines, forty peer-reviewed studies were systematically selected and analyzed to identify dominant error types and underlying factors in first-language acquisition contexts. The findings reveal that omission, word order errors, subject–verb disagreement, and overgeneralization are the most frequently reported syntactic errors, reflecting ongoing grammatical development rather than language impairment. The review further identifies developmental stage, limited exposure to complex linguistic input, cognitive processing constraints, and classroom practices as key contributing factors. These findings highlight the importance of linguistically rich interaction and informed pedagogical strategies to support syntactic development in early childhood education settings.